WATER BALANCE ASSESSMENT IN THE ANTHROPOGENICALLY LOADED CATCHMENT AREA OF THE ZERAVSHAN RIVER (UZBEKISTAN) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The water balance components of the river basin of the River Zeravshan, which is characterized by significant anthropogenic load, are considered. The hydrometeorological study of the territory is assessed, the statistical hydrological characteristics are analyzed, and the significance of trends in the series of observations of air temperature, precipitation and river runoff is assessed. It is found that trends are present only in two of the eight series of observations of temperature, the hydrological series and series of precipitation do not have trends. The evaporation calculation formulas are assessed. The water balance assessment showed that the incoming component is spent almost entirely on the catchment area of the River Zeravshan, including the use of water for industrial and municipal purposes.
Keywords: river runoff; precipitation; evaporation; trends; statistical characteristics; anthropogenic load